2019
DOI: 10.3174/ajnr.a6175
|View full text |Cite
|
Sign up to set email alerts
|

Zero TE MRI for Craniofacial Bone Imaging

Abstract: Zero TE MR imaging is a novel technique that achieves a near-zero time interval between radiofrequency excitation and data acquisition, enabling visualization of short-T2 materials such as cortical bone. Zero TE offers a promising radiation-free alternative to CT with rapid, high-resolution, silent, and artifact-resistant imaging, as well as the potential for "pseudoCT" reconstructions. In this report, we will discuss our preliminary experience with zero TE, including technical principles and a clinical case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 29 publications
(51 reference statements)
0
23
0
1
Order By: Relevance
“…Wiesinger et al [ 13 ] focused on ZTE with a scan time of 6 min 12 s required to acquire the high-resolution imaging necessary to create 3D reconstructed imaging. Lu et al [ 11 ] reported improved scan times of 4–5 min by using two separate ZTE acquisitions per patient. In their study, they imaged 14 patients aged between 3 months and 17 years with various pathologies, but provided only one example of the representative 3D output which appeared to be from an adult (no data provided).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wiesinger et al [ 13 ] focused on ZTE with a scan time of 6 min 12 s required to acquire the high-resolution imaging necessary to create 3D reconstructed imaging. Lu et al [ 11 ] reported improved scan times of 4–5 min by using two separate ZTE acquisitions per patient. In their study, they imaged 14 patients aged between 3 months and 17 years with various pathologies, but provided only one example of the representative 3D output which appeared to be from an adult (no data provided).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrashort echo time (UTE) and more recently zero echo time (ZTE) imaging have been increasingly used to evaluate structures with the shortest T2 values, with demonstrated benefits in PET/MRI attenuation correction, with demonstrable segmentation success within the skull [ 1 , 10 ]. Unlike the conventional RF pulse sequences, the ZTE sequence begins a readout period immediately after the RF pulse, thus permitting visualisation of short T2 materials [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the future, novel MR imaging techniques may bring further advances in mastoid imaging and visualization of bony structures or their pathology. Sequences like black bone [27,28] and ultrashort or zero echo-time (UTE and ZTE) [29,30] or their further developments [31] with relevant postprocessing may create images with a positive bone contrast similar to CT, thereby facilitating a more intuitive interpretation by surgeons. Their true additional diagnostic potential in temporal bone MR imaging remains to be seen and may be limited by the site-specific factors such as small details and air in the pneumatized bone.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical applications of UTE/ZTE MRI are steadily growing. However, to the best of our knowledge, there are few 3D printing studies or reports based on images obtained from UTE/ZTE MRI sequences 96,97 . We believe that 3D printing and UTE/ZTE MRI have great potential to grow synergistically.…”
Section: Orthopedic Surgerymentioning
confidence: 94%
“…Although the craniomaxillofacial (CMF) specialty was one of the earliest fields to adopt the use of 3D models derived from medical imaging data 101,102 and the usage of CT data over MRI data to create CMF models for presurgical planning is an accepted practice, 103 our search did not find any articles utilizing MRI for surgical planning of CMF procedures. With the introduction of novel black bone and UTE/ZTE MRI sequences, the use of MRI could become more prevalent in these case types 96 …”
Section: Other Considerations and Future Perspectivesmentioning
confidence: 99%